Traditional Cultures and Contemporary Changes: Kokonuco Ethnic People and Information and Communication Technologies (icts) - Acosta Nates, Paola Andrea (Desafíos, 2014)
Under a policy of “inclusion”, the state has made a generalized effort to promote the spread of icts within indigenous peoples, using different projects and strategies. In Colombia, indigenous peoples have chosen different strategies in order to incorporate icts into their lifestyles, which, in turn, has enabled gradual change to develop social policy and communication links beyond the territorial dimension. The model of the gradual appropriation of technology within the Kokonuco indigenous peoples located in the Cauca region of Colombia is analyzed through an anthropology of technology and particularly through the ethnography of socio-communicative internet networks. The concern with the problem of the use and appropriation of icts in indigenous peoples tries to answer the following question: How are icts perceived, socially appropriated and re-signified in the Kokonuco indigenous peoples?